An optical fibre sensor for physiological bending monitoring in clinical environment - Mohd Anwar, Zawawi (2015)
Health monitoring applications in clinical environment include various areas such as respiration assessment, heart rate monitoring, gait monitoring, spine bending as well as lower and upper limb motion detections. In human spine monitoring application, static and dynamic assessments of the spine bending are important and are generally preferrable as routine diagnostic procedures among chronic and acute low back pain patients. Many accurate and highly reliable devices are widely available for this application, such as computer tomography, fluoroscopy and magnetic resonance imaging technology, but they are potentially hazardous for repetitive use as well as being expansive for wide application. Alternatively, various non-invasive devices have been introduced, which are aimed for human spine assessment. They offer diverse characteristics and measurement performance, but most of them do not provide 20 continuous measurement that is required for spine assessment in sagittal and frontal planes. In this thesis, a low-cost plastic optical fibre bending sensor based on the intensity modulation is proposed, which bending angle is proportional to the tilting angle between two separated fibres. The sensor provides automatic intensity referencing via a divided beam system to compensate for the light source signal fluctuation and the propagation loss within the optical fibres. The inherited advantages of the optical fibre make it possible to develop a small probe size, lightweight, low costs as well as immune from electromagnetic interference, make it suitable for clinical application.